Relationship between Driving Anger, Support for Counter Measure, Situational Factors and Driving Behavior among Drivers in Malaysia - Nor Azimah Chew Abdullah; Nazlina Zakaria (International Journal of Supply Chain Management, 2018)
This study aims to investigate driving anger, support for counter measures, and situational factors affect drivers' driving behavior. One important reason for studying driver's aggression is that it has been cited as a frequent contributing factor in traffic collisions.